Carbon nanoparticles combined with indocyanine green for sentinel lymph node detection in endometrial carcinoma. Issue 3 (4th June 2021) - Liang, Sichen; Wang, Zhiqi; Chen, Jiayu; Yang, Xin; Liang, Xudong; Sun, Xiuli; Li, Xiaowei; Zhou, Rong; Li, Yi; Wang, Jianliu
Abstract: Objective: To evaluate the feasibility and clinical value of the combination of carbon nanoparticles (CNPs) and indocyanine green (ICG) for identifying sentinel lymph nodes (SLNs) in endometrial cancer. Materials and Methods: About 153 patients with endometrial cancer were recruited from July 2015 to May 2019. All patients underwent SLN biopsy according to the SLN algorithm for surgical staging with ICG and/or CNPs. The detection rate, factors associated with the detection rate, sensitivity, and negative predictive value (NPV) of SLNs were analyzed. Results: The detection rates of SLNs with the combined method were the highest among the different methods. As calculated per hemipelvis, the sensitivity and NPV with ICG alone or with ICG plus CNPs were 100%. With CNP, tumor Grade 3 and laparoscopy were related to unsuccessful overall SLN mapping while tumor diameter greater than 2 cm and laparoscopy were statistically associated with failed bilateral mapping. With ICG, a higher body mass index was significantly associated with unsuccessful bilateral detection of SLN. Conclusion: SLN assessment in endometrial cancer is feasible and safe with high sensitivity and high NPV when ICG and CNPs are combined and in low‐risk patients. It is a superior option to use CNPs in laparotomy for patients with endometrial cancer.